The publishing house of the National University Federico Villarreal and its contribution to Peruvian Quechua literature at the end of the 20th century and the beginning of the 21st century - Pérez Orozco, Edith Eliana (2024)
From 1997 to 2014, the Universidad Nacional Federico Villarreal, through its university publishing fund, promoted literary competitions in poetry and short stories in native languages, which allowed the visibility of Quechua writers from all regions of Peru (Ancash, Ayacucho, Cerro de Pasco, Cusco, Huancavelica, Trujillo, Lima). Thus, the Federico Villarreal National Quechua Literature Competition was launched and, almost immediately, the winning books were published in the Biblioteca de Cultura Quechua Contemporánea (Library of Contemporary Quechua Culture). In addition, the Federico Villarreal National University Novel Prize was promoted, which re-published, between 1998 and 1999, five volumes of La sangre de los cerros by the brothers Rodrigo, Luis and Edwin Montoya. It is important to emphasise that the bilingual translation of the poetry collection Los heraldos negros by César Vallejo (2002) was carried out by the Ayacucho writer Porfirio Meneses; and the research work by Dr. Espino Relucé, Atuqpacha. Memoria y tradición oral en los Andes (2014). In the current study, fourteen books related to Quechua literature were studied and interpretative textual analysis was applied as a methodology; in addition, documents such as Rectorial Resolutions of the UNFV from 2001 to 2012 were reviewed. Thus, it is concluded how this university contributed to the establishment and evidence of the literary canon of contemporary Quechua literature in the late twentieth century and early twenty-first century through its university publishing fund, by anticipating the linguistic, literary and cultural policy projects in native languages in Peru.